Improved human-computer interaction for mechanical systems design through augmented strain/stress visualisation. (2017) - Naets, Frank; Cosco, Francesco; Desmet, Wim
It is difficult to obtain realistic stress and strain estimates for mechanical designs due to unknown operational conditions, input forces and/or parameters. This limits a designer in evaluating whether a certain product meets all design specifications. This work presents an extended Kalman filter to obtain accurate strain and stress estimates of a structure under operational loading. An augmented reality application allows visualisation of these strains and stresses on a real component. This leads to an effective human-computer interface to evaluate a physical prototype. The developed approach exploits parametric reduced order models based on high fidelity finite-element design models to obtain an efficient formulation. This paradigm is validated on a flexible beam with unknown input forces and length. The proposed approach permits a more natural visualisation and interpretation of operational conditions. Our results encourage the adoption of this approach in applications ranging from design validation to online monitoring of structural components.